Penyuluhan Manajemen, Komunikasi Digital, dan Branding Usaha Pertanian, Peternakan, dan UMKM Desa Pringkasap Kabupaten Subang - Maharani Imran; Eka Rakhmat Kabul; Bida Sari; Shafenti Shafenti; Nur Wahyuni; Mahzumi Mahzumi; Rinaldi Rinaldi (IKRA-ITH ABDIMAS, 2023)
Knowledge and understanding of agricultural management and the use of digital communicationtechnology are essential in agriculture and village MSMEs. Lecturers from the University of PersadaIndonesia YAI conduct training on agricultural management, digital communication, and branding to enablefarmers and MSME stakeholders to expand their business to local, national, or international markets.Farmers and MSME actors are motivated to use digital communication media such as social media, websites,smartphone applications and others. The method used in this community service activity is to provideextension services to 31 farmers and MSME actors in Pringkasap village, Pabuaran district, Subang regency,West Java province, Indonesia. The result of this community service activity is an increase in knowledge aboutthe importance of agricultural management, digital communication, and branding for sustainablecommunication of products and brands. The results of this activity indicate that further training onagricultural management, digital communication, and branding is needed, not only with the extensionmethod, but also with the simulation method using complete materials and tools that can be applied directlyat the business site. MSME actors need to be trained in the use of computer and smartphone applications,and it is necessary to establish a special forum for business development.